Factors contributing to psychiatric patients abscondment at Zomba Mental Hospital - Musasa, Silvester (Kamuzu University of Health Sciences, 2022)
Mental illness is one the leading cause of disability in most of the developing and developed countries. The impact can be reduced by actively participating in an individual treatment plan in the hospital. However, issues of psychiatric patients leaving the hospital with no authorization from hospital staff stand a global challenge considering the consequences that comes eventually.Zomba Mental Hospital is one of the psychiatric hospital in Malawi which is facing this problem. Measures have been put in place to curb the problem but still abscondment remains a challenge among male and female patients,